2005
DOI: 10.1038/nature03707
|View full text |Cite
|
Sign up to set email alerts
|

Glass transition in hyperquenched water?

Abstract: It has been unclear whether amorphous glassy water heated to around 140-150 K remains glassy until it crystallizes or whether instead it turns into a supercooled and very viscous liquid. Yue and Angell compare the behaviour of glassy water under these conditions to that of hyperquenched inorganic glasses, and claim that water stays glassy as it heats up to its crystallization point; they also find a 'hidden' glass-to-liquid transition at about 169 K. Here we use differential scanning calorimetry (DSC) heating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
90
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 9 publications
6
90
2
Order By: Relevance
“…However, our study reveals that both HDL and LDL can be observed experimentally, and in terms of fragility, the transformation from HDL to LDL involves a dynamic crossover from a less strong to a very strong liquid. This finding settles a long-standing question in understanding water, in which LDL near 140 K was postulated to be "strong" (8,(52)(53)(54)(55), "not strong" (56), "not fragile" (9,11,57), or "the strongest liquid yet identified" (58). In fact, our temperature-dependent dielectric and heating-rate-dependent calorimetric data classify LDL as a "superstrong" liquid (59), which shows the lowest steepness index m 1 = 14 ± 1 of all liquids.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, our study reveals that both HDL and LDL can be observed experimentally, and in terms of fragility, the transformation from HDL to LDL involves a dynamic crossover from a less strong to a very strong liquid. This finding settles a long-standing question in understanding water, in which LDL near 140 K was postulated to be "strong" (8,(52)(53)(54)(55), "not strong" (56), "not fragile" (9,11,57), or "the strongest liquid yet identified" (58). In fact, our temperature-dependent dielectric and heating-rate-dependent calorimetric data classify LDL as a "superstrong" liquid (59), which shows the lowest steepness index m 1 = 14 ± 1 of all liquids.…”
Section: Discussionmentioning
confidence: 83%
“…The occurrence of water's ambient pressure glass transition at T g,1 = 136 ± 2 K (4-6) has been discussed controversially for almost five decades mainly because its calorimetric signature is very feeble (7). Even though the question about the nature of this transition has not been settled ultimately, recent work interprets this signature to be consistent with a glass-toliquid transition and places deeply supercooled water into the category of "strong" liquids (8)(9)(10)(11). Lately, it has become clear that water's high-density phase exhibits a glass transition at pressures ≥0.1 GPa, which has also been interpreted in terms of a glass-to-liquid transition (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…In these cases, crystallization interferes at a temperature about 14 K above T g and the C p increases in this range are ð1.9 AE 0.2Þ J mol −1 K −1 (2) and ð1.6 AE 0.2Þ J mol −1 K −1 (3) for the glassliquid transition of ASW and HGW, respectively. † (In a later study (17), a smaller value of 0.7 J mol −1 K −1 was reported for HGW.) Thus, the heat capacity rise for HDA is larger.…”
Section: Resultsmentioning
confidence: 99%
“…Water molecules have been reported to gain rotational freedom at the glass transition (Fisher & Devlin, 1995) and to exhibit translational diffusion just above, at 150 K (Smith & Kay, 1999). However, the existence of ultraviscous water in the temperature range between 136 and 150 K remains controversial (Kohl et al, 2005;Yue & Angell, 2004) and a direct transformation from the glassy to the crystalline state at 150-160 K has been proposed (Velikov et al, 2001). In any case, liquid bulk water cannot be studied experimentally at temperatures between 150 and 235 K, the so-called 'no man's land' (Mishima & Stanley, 1998).…”
Section: Temperature-dependent Behaviour Of Protein Crystalsmentioning
confidence: 99%